"I’m strong within myself": Gender, class and emotional capital in childcare - Andrew, Yarrow (British Journal of Sociology of Education, 2015)
Emotions have received increasing attention in educational circles in the last decade. Drawing on Bourdieu, feminist scholars use emotional capital to illustrate the ways gendered inequalities can compound the disadvantages of social class. This paper examines relationships within childcare services in Australia, showing how emotional capital functions as a resource for staff. Data from interviews with childcare staff illustrate key aspects of emotional capital, such as reflexivity, resilience and embodiment. Findings show that investing in emotional capital is the key to a long-lasting commitment to childcare work, and should be valued accordingly. © 2013 Taylor & Francis.
Keywords: 2000 à aujourd'hui; 2010-2019; australie; capital émotionnel; care; discipline; maternité; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; service de garde; sociologie; thématiques; travail; travail du care

Stability and transformation in gender, work, and family: Insights from the second shift for the next quarter century - Blair-Loy, Mary; Hochschild, Arlie; Pugh, Allison J.; Williams, Joan C.; Hartmann, Heidi (Community, Work and Family, 2015)
Arlie Hochschild's The second shift: Working families and the revolution at home argued that the revolution toward gender equality in the USA has been stalled due to three factors: (1) women continue to do most of the ‘second shift’ – the unpaid work of childcare and housework; (2) insufficient flexibility in the workplace for accommodating family caregiving needs; and (3) a deficit of public sector benefits, such as paid parental leave. Since the book's publication in1989, many aspects of the gender structure (how gendered opportunities, barriers, and cultural meanings are socially structured in the USA) remain the same. Yet many aspects have changed. This article looks at areas of stability in the gender structure and areas of transformation in the past quarter century. We then plumb the book for the analytical insights it generates for scholars today. We discuss how deep-seated cultural understandings of gender infuse all levels of analysis: macro-level policies, family and work institutions, and personal experiences of gender, intimacy, and moral commitments. These insights help illuminate paths forward for new research on how new economic developments, including economic insecurity, flexibilization (the increasingly reliance on temporary and contract labor), and the widening social class divide, continue to affect intimacy at home. © 2015 Taylor & Francis.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; discipline; double journée de travail; histoire et politique; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail domestique; états-unis

Food and femininity - Cairns, Kate; Johnston, Josée (Contemporary food studies: economy, culture and politics, 2015)
"Over the space of a few generations, women's relationship with food has changed dramatically. Yet -- despite significant advances in gender equality -- food and femininity remain closely connected in the public imagination as well as the emotional lives of women. While women encounter food-related pressures and pleasures as individuals, the social challenge to perform food femininities remains: as the nurturing mother, the talented home cook, the conscientious consumer, the svelte and health-savvy eater. In Food and Femininity, Kate Cairns and Josée Johnston explore these complex and often emotionally-charged tensions to demonstrate that food is essential to the understanding of femininity today. Drawing on extensive qualitative research in Toronto, they present the voices of over 100 food-oriented men and women from a range of race and class backgrounds. Their research reveals gendered expectations to purchase, prepare, and enjoy food within the context of time crunches, budget restrictions, political commitments, and the pressure to manage health and body weight. The book analyses how women navigate multiple aspects of foodwork for themselves and others, from planning meals, grocery shopping, and feeding children, to navigating conflicting preferences, nutritional and ethical advice, and the often-inequitable division of household labour. What emerges is a world in which women's choices continue to be closely scrutinized -- a world where 'failing' at food is still perceived as a failure of femininity. A compelling rethink of contemporary femininity, this is an indispensable read for anyone interested in the sociology of food, gender studies and consumer culture."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; inégalités; ontario; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques; toronto; travail

Sociologie du genre - Clair, Isabelle (Armand Collin, 2015)
Traduit de l'anglo-américain, le concept de genre s'est progressivement imposé en France au cours des quinze dernières années. Il recouvre désormais un corpus incluant d'autres concepts qui l'ont précédé, tels que «rapports sociaux de sexe» ou «domination masculine». L'objectif de ce manuel est de mieux cerner la polysémie du genre et d'introduire aux recherches prolifiques qui sont rassemblées sous sa bannière. Tous les travaux de la sociologie du genre ont en commun une problématique : la construction sociale de la différence hiérarchisée des sexes et/ou des sexualités ; une histoire, commencée dans les années 1970, ancrée dans une critique féministe de la sociologie de l'époque qui voyait dans la classe sociale le seul clivage pertinent pour analyser les relations sociales ; une ambition : faire la preuve, enquête après enquête, de la transversalité des rapports de sexe et de sexualité dans le monde social, et convaincre de la nécessité de leur prise en compte dans l'élaboration de n'importe quel objet sociologique.
Keywords: approches et analyses; discipline; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexualité; sociologie; thématiques; travail

School's out: Gay and lesbian teachers in the classroom - Connell, Catherine (University of California Press, 2015)
Comment les enseignants gays et lesbiens négocient-ils leurs identités professionnelles et sexuelles au travail, alors que ces identités sont construites comme s’excluant mutuellement, voire comme s’opposant mutuellement ? À l'aide d'entretiens et d'autres documents ethnographiques du Texas et de Californie, School's Outexplore comment les enseignants luttent pour créer une personnalité de classe qui équilibre qui ils sont et ce que l'on attend d'eux dans un climat d'homophobie omniprésente. L'examen par Catherine Connell de la tension entre la rhétorique de la fierté gay et l'éthique professionnelle de la discrétion relie et considère de manière perspicace des facteurs compliquants, depuis la loi et la politique locales jusqu'au privilège de genre. Elle décrit également comment les discours racialisés sur l’homophobie contrecarrent les contestations des injustices sexuelles dans les écoles. Écrit avec une verve ethnographique, School's Out est une lecture essentielle pour les spécialistes et les étudiants des études queer, des études de genre et des politiques éducatives.
Keywords: amériques; discipline; identités LGBTQIA2+; pédagogie; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; travail; états-unis

Taire ou exposer la diversité sexuelle ? Impacts des normes de genre et de l'hétéronormativité sur les pratiques enseignantes - Richard, Gabrielle (Genre, sexualité & société, 2015)
À partir de 22 entretiens et de 243 questionnaires d’enquête complétés par des enseignants du secondaire du Québec (Canada), cet article interroge l’existence de normes relatives au genre et à l’orientation sexuelle en milieu scolaire. Les résultats suggèrent que les pratiques professionnelles des enseignant(e)s, tant lesbiennes, gais et bisexuels (LGB) qu’hétérosexuel(le)s concernant l’homophobie et la diversité sexuelle sont influencées par ces normes. Trente ans après les premiers travaux sur le vécu des enseignants LGB, la littérature sur le coming out demeure centrale pour comprendre les pratiques professionnelles de ceux-ci ainsi que leurs appréhensions. Based on 22 interviews and 243 survey questionnaires filled out by high school teachers in Québec (Canada), this paper questions the existence of norms relating to gender and sexual orientation in schools. Results suggest that teachers’ professional practices regarding homophobia and sexual diversity are influenced by these norms, whether they identify as heterosexual or as lesbian, gay or bisexual (LGB). Thirty years after the first studies on LGB teachers’ experiences, the coming out literature remains central to the understanding of teachers’ apprehensions and fears, as well as their pedagogical practices.
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; homophobie; hétérosexisme; identités LGBTQIA2+; québec; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire; étude qualitative; étude quantitative

The pedagogical practices of Québec high school teachers relative to sexual diversity - Richard, Gabrielle (Journal of LGBT Youth, 2015)
This article explores the ways in which teachers describe their pedagogical and intervention practices relative to sexual diversity in Québec (Canada). Three variables closely associated with teachers who report inclusive practices emerge: experiential training (based on the experience of a lesbian, gay, or bisexual [LGB] teacher), contact training (from close acquaintance with LGB individuals), and professional training. These factors impact the probability that a teacher will refer to homosexuality, intervene when homophobic incidents occur to deconstruct prejudices, and become the confidant of LGBQ students. Results are discussed based on research on minority teachers and on the roles of straight allies in education.
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; formations; homophobie; hétérosexisme; identités LGBTQIA2+; outils; québec; ressource en ligne; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire

La différence sexuelle au cabinet des anthropologues parisiens à la fin du XIXe siècle - Rodriguez, Eva (Emulations - Revue de sciences sociales, 2015)
Dans le dernier tiers du XIXe siècle, l’anthropologie biologique, et a fortiori, l’anthropométrie, se consacre en France comme une démarche scientifique que la standardisation des méthodes et des instruments doit garantir. Reposant sur un naturalisme direct, elle se présente comme une entreprise d’objectivation et de hiérarchisation des différences, principalement raciales. Dans cet article, il s’agit d’étudier comment, dans ce corpus anthropologique (notamment dans les travaux de la Société d’Anthropologie de Paris) la différence sexuelle, qui pouvait troubler les classifications raciales, va être redéfinie comme une différence variable selon les races, au risque de saper les fondements naturalistes sur lesquels repose cette différence des sexes.
Keywords: 1800-1899; 1870-1879; 1880-1889; 1890-1899; anthologie; approches et analyses; cours; discipline; discours dominant; europe; france; justice sociale; paris; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail

Gendered emotion work around physical health problems in mid- and later-life marriages - Thomeer, Mieke B.; Reczek, Corinne; Umberson, Debra (Journal of Aging Studies, 2015)
The provision and receipt of emotion work-defined as intentional activities done to promote another's emotional well-being-are central dimensions of marriage. However, emotion work in response to physical health problems is a largely unexplored, yet likely important, aspect of the marital experience. We analyze dyadic in-depth interviews with husbands and wives in 21 mid- to later-life couples to examine the ways that health-impaired people and their spouses provide, interpret, and explain emotion work. Because physical health problems, emotion work, and marital dynamics are gendered, we consider how these processes differ for women and men. We find that wives provide emotion work regardless of their own health status. Husbands provide emotion work less consistently, typically only when the husbands see themselves as their wife's primary source of stability or when the husbands view their marriage as balanced. Notions of traditional masculinity preclude some husbands from providing emotion work even when their wife is health-impaired. This study articulates emotion work around physical health problems as one factor that sustains and exacerbates gender inequalities in marriage with implications for emotional and physical well-being. © 2014 Elsevier Inc.
Keywords: amériques; approches et analyses; couples hétérosexuels; discipline; mariage; projet charge mentale; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail invisible; travail émotionnel; vieillissement; états-unis

Sous le développement, le genre - Verschuur, Christine; Guérin, Isabelle; Guetat-Bernard, Hélène (Objectifs Suds, 2015)
Du site de l'éd. : Ignorée, invisible, la question du genre reste cachée sous le développement. Et pourtant, comprendre le développement n'est pas possible sans une perspective de genre. Cet ouvrage, didactique, montre en quoi et comment le concept de genre permet de revisiter les études de développement. Le genre permet de comprendre la construction historique, sociale et culturelle des diffé- rences et des inégalités. Il offre des outils pour une analyse critique du système capitaliste globalisé. Le genre, inscrit dans le féminisme, permet aux catégories dominées et marginalisées, en particulier les femmes mais pas seulement, de faire entendre leurs voix. Dans le contexte actuel de crise globale et d'accroissement des inégalités, il propose des pistes pour renouveler la pensée sur le développement, mais aussi pour agir autrement. Combinant diverses disciplines et thématiques, cet ouvrage montre que la portée heuristique du genre ne se limite pas aux domaines habituellement considérés comme féminins (l'éducation, la famille, le social, la santé de la reproduction, etc.) mais s'étend à tous les domaines (le politique, le droit, la sécurité, la diplomatie, l'économie, etc.).Ce livre met aussi en évidence la diversité et l'enrichissement mutuel des diverses traditions de recherche entre le monde francophone, anglophone et hispano- phone. Il s'adresse particulièrement aux personnes étudiantes, chercheures et enseignantes, militantes, chargées de programme dans des organisations de coopération et représentantes des pouvoirs publics au Nord et au Sud.
Keywords: agriculture; anthropologie; approches et analyses; corps; cours; discipline; droit; environnement; féminisme décolonial; féminisme matérialiste; justice sociale; migration; pol4022; premier cycle; rapports sociaux de sexe; relations internationales; ressource en ligne; science politique; science politique et droit; sciences de la gestion; sciences humaines; sociologie; thématiques; travail; économie